Prediction Analysis on Coefficient of Consolidation Values in Improved Soft Clays - Fitriani, Eka Nur; Aspar, Wimpie Agoeng Noegroho; Arthono, Andri; Fiantika, Thiya (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2023)
Consolidation is a phenomenon in soil mechanics that often causes geotechnical problems. One solution to overcome consolidation phenomena is by speeding up process of pore water pressure dissipation. The type of soil improvement to upgrade the performance of soft clay is by applying pre-fabricated vertical drain (PVD) and pre-compression simultaneously. Geotechnical instrumentations such as settlement plates, piezometers, and inclinometers were installed at the field of study to monitor magnitude of settlement during consolidation process. After the final settlement was achieved, the consolidation parameters such as coefficient of consolidation, and rate of settlement, were back calculated. Prediction analysis of consolidations parameters was performed by means of Asaoka method. The results of this study is very interesting and provide useful engineering information. It is interesting to note that this case study may be beneficial use to practicing engineers and researchers.